Registration of fishing boats - Mumbai Archive Project Team (Jio Institute, 2024)
Fishing boats must be registered with the relevant maritime authorities, such as the Maharashtra Maritime Board (MMB) or the Mercantile Marine Department (MMD). Additionally, boat owners and operators may need to obtain licenses or permits to operate their vessels legally. These licenses may include fishing permits, vessel registration certificates, and crew licenses.